Assessment of the spatiotemporal evolution and driving forces of meteorological drought in the North China Plain - Yang, Cuiping; Liu, Changhong; Wang, Yongqiang; Gu, Yuhui; Ma, Xiaoyi (International journal of climatology, 2023)
With the changing trend of global temperature increase, the occurrence of drought events can no longer be ignored. An investigation of the spatiotemporal evolution characteristics of meteorological droughts and their responses to climatic variables can elucidate the mechanisms of the water cycle evolution in changing environments. In the present study, the standardized precipitation evapotranspiration index was used to characterize meteorological drought in the North China Plain (NCP) from 1970 to 2020. The spatiotemporal patterns of meteorological drought were analysed, and the contributions of climatic factors on annual and seasonal time scale drought evolution were determined. The results revealed that meteorological drought showed a decreasing trend (−0.07/10a) in the NCP from 1970 to 2020 and the most severe meteorological drought occurred in winter, with 56.56% of the region experiencing an increased drought trend in this season. Significant trends were identified for mean temperature (Tmean), temperature difference, and wind speed in the drought trend evolution. Precipitation (P) and Tmean were the primary controlling factors of the drought evolution. The strongest effect on drought change were exerted by P in spring (contribution [Con]: 1.57%), summer (Con: 1.79%) and autumn (Con: 2.43%), and the negative contribution of Tmean in winter (Con: −3.64%) was greater than the positive contribution of P (Con: 2.69%). The contribution of climatic variables to drought were increased by regional altitude difference. The results reveal a novel explanatory mechanism of climate change's effects on drought. Evolution of meteorological drought and assessment of its drivers in the North China Plain.